Constipation - Mózsik, Gyula (IntechOpen, 2019)
Constipation is a problem with multifactorial origin that affects both children and adults. It is a difficult problem to treat because there is no clear diagnostic criteria and there are only limited therapeutic options. This book presents information on constipation, including pathology, diagnosis, imaging, nutrition, and management, among other topics. It is written for physicians and interested readers alike.